Enhancing the Immunogenicity of Subunit Vaccines by Utilisation of Particulate Vaccine Delivery Systems - Anggia Prasetyoputri; Wien Kusharyoto (ANNALES BOGORIENSES, 2013)
Control and eradication of a number of infectious diseases are primarily attributed to effective vaccination programs. A concerted effort is still imperative to develop novel vaccines and improve the immunogenicity of existing ones with regards to efficacy, immunogenicity and safety. Rational design of vaccines using subunit vaccines is a potentially safer alternative to conventional vaccines, yet they are poorly immunogenic without additional adjuvant. Using antigen carriers to enhance their immunogenicity in the forms of adsorption or encapsulation with a delivery system has been widely investigated as an alternative to currently available adjuvants. This review aims to elaborate on the existing nanotechnology being used to develop more immunogenic subunit vaccines, with focus on particulate delivery systems for development of prophylactic vaccine candidates.